Monks, Monarchs and Mountain Folks: Domestic Tourism and Internal Colonialism in Northern Thailand - Olivier Evrard (2018)
The development of domestic (or national) tourism in Thailand in the second half of the 20th century relied on a new kind of relationship between the state and local cultures. Rural spaces have been reinvented and transformed into appealing visual and conceptual archetypes which sustain discourses on both local and national identity and history. Thai tourism allows a kind of pacification of the relations between the centre and the periphery, but it also perpetuates an internal colonialism, both towards Tai and non-Tai populations. This article investigates the social significance of domestic tourism in Chiang Mai and the links between non-Western representation of travel, nationalism and localized identity. It focuses on three attractions scattered along the road going up to the mountain of Suthep (Doi Suthep), one of the most famous tourist destinations in northern Thailand: a Buddhist temple, a royal palace and an ethnic village. These three attractions provide crucial insights into the history of domestic tourism in Thailand: its similarities to and differences from previous forms of travel, its relations to the idealization of the rural and its role in the pacification of the relations between the Thai state and its geographic and social margins. © The Author(s), 2009.